Impact of Declining Operational Efficiency on the Production Capacity of Power Plants: A Case Study of the Zawiya Combined Power Station - عبد العظيم محمد الخضراوي; حسان حسين عريبي; محمد البشير محمد الدخيلي (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aims to examine the decline in operational efficiency and its impact on the production capacity of the Zawia Combined Power Station by evaluating the actual performance of one gas turbine unit. The methodology was based on collecting operational data from the daily control room reports over a six-month period (from January 16 to June 16, 2023), followed by analysis using standard equations for estimating efficiency and production capacity. The results indicated that the average efficiency during the study period was 27.5%, compared to the design efficiency of 35%, representing a decrease of 7.5%. This decline was reflected in the generated power, which dropped from 165 MW to approximately 127 MW, resulting in a deficit of 38 MW per hour per unit and a daily deficit of around 912 MWh over 24 hours of operation for each unit. When these findings are extrapolated to all six units of the station, the total loss in production capacity is estimated at approximately 5,472 MWh per 24-hour operational cycle, representing a significant loss at the power generation system level. The main causes of this decline include non-compliance with the preventive maintenance schedule, unavailability of original spare parts, and issues within the national grid such as frequency fluctuations and synchronization problems. The results also revealed that the type of fuel used has a noticeable effect on performance; thermal efficiency was higher when operating the turbines with natural gas compared to liquid fuel, with a difference of 4.5%. The study concludes with a recommendation to improve maintenance programs and ensure the availability of appropriate spare parts. It also emphasizes the need for future studies on the impact of operational factors and fuel types on efficiency, in order to enhance the station’s reliability and reduce future deficits in production capacity.